Education in the 21st century - Tomé, José Manuel Salum (Seven Editora, 2024)
The thesis project presented below essentially aims to develop a model (instruments) for evaluating the performance of students according to the competencies required according to the modular curriculum and the graduation profile of those in the specialty of graphics, in accordance with the Professional Profile. This model will be composed of three main categories of content: Intellectual Competencies, Conditions of Efficiency; and General Competencies, each of which is made up of a certain number of competencies, which in turn are broken down into Performances and will be elaborated through the collection of background information through interviews and structured surveys to leading organizations in the educational and business sector of the commune and region. and teachers of the specialty of graphics. Based on the results, the competencies will be classified according to the level of importance of the same to the efficient performance of the students and according to the current level of the demands of each of them in the world of work, which will allow to determine the needs of deepening that should be taken into account for learning in the Lyceum and thus achieve the Graduate and Professional Profile according to the labor reality. The results of the research will allow us to evidence existing gaps in the Performance for the achievement of the Competencies of the students in the Vocational Technical High School, which would lead to the search for methodological strategies that lead to the achievement of the Competencies in the modular curriculum; thus allowing the development of instruments to evaluate the performance of students in relation to the labor competencies (required according to the graduation profile) In addition, this standardised assessment model will have to allow us to measure the level of reading and writing, mathematics, language, etc.basic skills required by the labour market. We will facilitate the implementation of curricular content that increases students’ ability to undertake, make responsible decisions and analyze problems in a systemic way, and that nurture creativity, autonomy and responsibility at work. We will encourage the existence of educational projects that promote entrepreneurship. DOI:https://doi.org/10.56238/sevened2024.007-055